Discussion & Recommendations - Nillesen, Anne Loes (A+BE | Architecture and the Built Environment, 2018)
The proposed methodology creates opportunities for designers to actively participate in debates concerning the location, layer, and scale of flood risk management interventions, resulting in a more integrated design approach. The systematic approach and the strong connection to variables and data sets provides a framework that makes it easier to communicate designers’ propositions from a spatial point of view to engineers and facilitates interdisciplinary cooperation. The developed sub-method for evaluating interventions at different flood risk levels, to shift flood risk management interventions to the most suitable locations, offers a framework for developing a combined probability and consequence reduction strategy. This method can become a valuable tool for strategy development and decision making in so-called multi-layered flood risk management approaches, in which interventions regarding the probability and the consequential damage of a flood are combined. Multi-layered safety approaches have often been referred to in flood risk management debates in the Netherlands, but so far, consistent methods for achieving a balanced probability and consequence reduction strategy have not been put in place.